2011
DOI: 10.1177/104063871102300223
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Chlamydiaceae, Mycoplasma Conjunctivae, and Pestiviruses in Alpine Chamois (Rupicapra r. Rupicapra) of Grisons, Switzerland

Abstract: Abstract. Because interactions between livestock and chamois occur on Alpine pastures, transmission of infectious diseases is considered possible. Thus, the occurrence of Chlamydiaceae, Mycoplasma conjunctivae, and pestiviruses in Alpine chamois (Rupicapra r. rupicapra) of the Surselva region (eastern Swiss Alps) was investigated. In total, 71 sera, 158 eye swabs, 135 tissue samples, and 23 fecal samples from 85 chamois were analyzed. The sera were tested by 2 enzyme-linked immunosorbent assay (ELISA) kits spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
17
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 27 publications
3
17
1
Order By: Relevance
“…Polkinghorne et al (2009) identified chlamydial species colonizing the conjunctiva of otherwise healthy animals but could not link the identification to subsequent disease onset. In the animals in our current study, chamois 515 L was the only animal with evident pathology that was shedding very low levels of C. pecorum but had a diagnosed coinfection with Mycoplasma conjunctivae (Holzwarth et al 2011b). Subsequently, M. conjunctivae was also associated with infectious keratoconjunctivitis in chamois (Mavrot et al 2012).…”
mentioning
confidence: 60%
See 2 more Smart Citations
“…Polkinghorne et al (2009) identified chlamydial species colonizing the conjunctiva of otherwise healthy animals but could not link the identification to subsequent disease onset. In the animals in our current study, chamois 515 L was the only animal with evident pathology that was shedding very low levels of C. pecorum but had a diagnosed coinfection with Mycoplasma conjunctivae (Holzwarth et al 2011b). Subsequently, M. conjunctivae was also associated with infectious keratoconjunctivitis in chamois (Mavrot et al 2012).…”
mentioning
confidence: 60%
“…The study centered on the canton of Grisons, Switzerland, where cograzing of wildlife and domesticated ruminants is common and where C. pecorum was identified in ibex (Holzwarth et al 2011a), chamois (Holzwarth et al 2011b), and red deer (Regenscheit et al 2012). Molecular typing of these C. pecorum-positive samples from both of these groups from the sympatric populations was not performed at the time and will be necessary to evaluate whether any ''spill-over'' or ''spill-back'' has occurred between the populations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A better understanding of the origin of C. pecorum in koalas will require a larger cohort of livestock and koala samples from the same geographical area in Australia. A broader assessment of the strains reported in other Australian marsupials (54) and worldwide domesticated and wild ungulates (55,56) would contribute to our understanding of the genetic diversity of C. pecorum and the origins of these infections. Such an analysis should also include a larger number of samples within each population to build a better picture of the intrapopulation C. pecorum genetic structures, thus improving our understanding of the epidemiology of these infections.…”
Section: Discussionmentioning
confidence: 99%
“…The spectrum of C. pecorum infections in livestock hosts ranges from subclinical to acute disease manifestations such as polyarthritis, sporadic bovine encephalomyelitis, pneumonia and conjunctivitis, with (asymptomatic) gastrointestinal shedding as the common feature 5 . C. pecorum infections in free-range ruminants such as Alpine ibex and chamois from Europe have also been reported 6,7 .…”
mentioning
confidence: 99%